Myocardial tissue characterization by contrast-enhanced cardiac magnetic resonance imaging in subjects with prediabetes, diabetes, and normal controls with preserved ejection fraction from the general population. (26th July 2017) - Storz, Corinna; Hetterich, Holger; Lorbeer, Roberto; Heber, Sophia D; Schafnitzel, Anina; Patscheider, Hanna; Auweter, Sigrid; Zitzelsberger, Tanja; Rathmann, Wolfgang; Nikolaou, Konstantin; Reiser, Maximilian; Schlett, Christopher L; et al.
Abstract: Aims: To characterize changes in the myocardium in subjects with prediabetes, diabetes, and healthy controls with preserved left ventricular ejection fraction (LVEF) by using cardiac magnetic resonance imaging (CMR) in a sample from the general population. Methods and results: Subjects without history of cardiovascular disease and preserved LVEF but established diabetes, prediabetes, and controls from a population-based cohort underwent contrast-enhanced CMR. Obtained parameters included left ventricular (LV) function and morphology, late gadolinium enhancement as well as T1-mapping and derivation of extracellular volume fraction (ECV) by modified Look-Locker inversion recovery for diffuse fibrosis in a subset of patients. Fibrosis volume and cell volume were calculated and LV remodelling index was calculated by dividing the LV mass by its end-diastolic volume. Among 343 subjects (56.1 ± 9.2 years, 57% males), 47 subjects were classified as diabetes, 78 as prediabetes, and 218 as controls. Haematocrit values and thus ECV parameters were available in 251 subjects. LV remodelling index was significantly higher in participants with prediabetes and diabetes, independent of body mass index (BMI), hypertension, age, and sex. ECV was decreased in subjects with prediabetes and diabetes compared with healthy controls (23.1 ± 2.4% and 22.8 ± 3.0%, both P  < 0.007). In contrast, cell volume was significantly higher in subjects with prediabetes and diabetes as compared with controls (109.1 ± 23.8 and 114.9 ± 32.3 mL vs. 96.5 ± 26.9 mL, both P  < 0.03, respectively). However, differences in ECV and cell volume attenuated after the adjustment for cardiometabolic risk factors, including age, sex, BMI, and hypertension. Conclusion: Subjects with prediabetes and diabetes but preserved LVEF had higher LV remodelling indices, suggesting early detectable changes in the disease process, while diffuse myocardial fibrosis appears to be less relevant at this stage.